Two recurrent mutations are associated with GNE myopathy in the North of Britain. Issue 12 (2nd April 2014) - Chaouch, Amina; Brennan, Kathryn M; Hudson, Judith; Longman, Cheryl; McConville, John; Morrison, Patrick J; Farrugia, Maria E; Petty, Richard; Stewart, Willie; Norwood, Fiona; Horvath, Rita; Chinnery, Patrick F; et al.
Abstract : Objective: GNE myopathy is a rare recessive myopathy associated with inclusion bodies on muscle biopsy. The clinical phenotype is associated with distal muscle weakness with quadriceps sparing. Most of the current information on GNE myopathy has been obtained through studies of Jewish and Japanese patient cohorts carrying founder mutations in the GNE gene. However, little is known about GNE myopathy in Europe where the prevalence is thought to be very low. Methods: Patients were referred through the National Specialist Commissioning Team service for limb-girdle muscular dystrophies at Newcastle (UK). All patients harbouring mutations in the GNE gene were recruited for our study. Detailed clinical and genetic data as well as muscle MRIs and muscle biopsies were reviewed. Results: We identified 26 patients harbouring mutations in the GNE gene. Two previously reported mutations (c.1985C>T, p.Ala662Val and c.1225G>T, p.Asp409Tyr) were prevalent in the Scottish, Northern Irish and Northern English populations; with 90% of these patients carrying at least one of the two mutations. Clinically, we confirmed the homogenous pattern of selective quadriceps sparing but noted additional features like asymmetry of weakness at disease onset. Conclusions: GNE myopathy is an important diagnosis to consider in patients presenting with distal leg muscle weakness. We report, for the first time, two common mutations in the north of Britain and highlight the broader spectrum of clinical phenotypes. We also propose that the prevalence of GNE myopathy may be underestimated due to the frequent absence of rimmed vacuoles in the muscle biopsy.